Enseignement du design numérique au 2e cycle universitaire: former à l’intervention professionnelle - Sperano, Isabelle; Roberge, Jacynthe; Kavanagh, Éric (My University, 2014)
This paper takes a look at the design education of a professional intervention in a master program in digital design. First, we present the evolution of this class and his actual characteristics. Then we describe and reflect on 3 key-aspects, particularly relevant in the context of design education: research, negotiation and preparation of the mandate, 2) problem setting and 3) definition of the solution and presentation deliverables. We particularly insist on issues relative to the student learning design, the relation between the student and the teacher and the relation between the student and the organisation.
Digital design education as part of a masters program
Keywords: design education; professional intervention; digital design; interaction design; information architecture; interface design